2013
DOI: 10.1155/2013/301369
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Synergistic Systems Model for Exploring the Efficacies of Different Chemotherapeutic Strategies in Cancer

Abstract: Different chemotherapeutic strategies like Maximum Tolerable Dosing (MTD), Metronomic Chemotherapy (MCT), and Antiangiogenic (AAG) drug are available; however, the selection of the best therapeutic strategy for an individual patient remains uncertain till now. Several analytical models are proposed for each of the chemotherapeutic strategies; however, no single analytical model is available which can make a comparative assessment regarding the long-term therapeutic efficacy among these strategies. This, in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Though different analytical and simulation based studies showed that the efficacies of such drugs may have better in control of tumor growth, different clinical reports suggest that these monoclonal antibody based drugs do not qualify towards the expected criteria of overcoming the physiological toxicity [ 22 , 23 ]. This, in turn, may limit the wider acceptance of AAG drugs for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Though different analytical and simulation based studies showed that the efficacies of such drugs may have better in control of tumor growth, different clinical reports suggest that these monoclonal antibody based drugs do not qualify towards the expected criteria of overcoming the physiological toxicity [ 22 , 23 ]. This, in turn, may limit the wider acceptance of AAG drugs for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest that most of the small molecular tyrosine kinase inhibitors have an immunomodulatory role [10]. Perhaps the greatest advantage of sAAG drugs in future could be used for targeted therapies by inserting in liposomes [11] or can be applied through MCT (metronomic dosing strategy, where chemotherapeutic drugs are applied with dose-dense mode i.e., very low doses but with a frequent intervals) strategy; hence can be applied orally [12][13][14][15][16][17][18]. There are several sAAG drugs now available for clinical use and the list is growing in number; however, most of them have a molecular weight ranges from 130 to 600.…”
Section: Introductionmentioning
confidence: 99%